2008
DOI: 10.1002/hlca.200890057
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Conformational Analysis of Pentapeptides Containing Enantiomerically Pure 2,2‐Disubstituted Glycines

Abstract: The synthesis and conformational analysis of model pentapeptides with the sequence Z‐Leu‐Aib‐Xaa‐Gln‐Valol is described. These peptides contain two 2,2‐disubstituted glycines (α,α‐disubstituted α‐amino acids), i.e., Aib (aminoisobutyric acid), and a series of unsymmetrically substituted, enantiomerically pure amino acids Xaa. These disubstituted amino acids were incorporated into the model peptides via the ‘azirine/oxazolone method’. Conformational analysis was performed in solution by means of NMR techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 84 publications
0
1
0
1
Order By: Relevance
“…4(4) φ ( -57.4 (7) -111.0 (5) 179.4 (4) -57(1); -52 (1) -50(1); -54 (1) 49.4 (6) 45.2 (6) (2) 163 (2) 3.052 (2) 171 (2) 3.013 (2) 166 (1) (S,S)-8e 3.007 (4) 165 (4) 2.872 (4) 166 (4) …”
Section: Z-gly-(s)-phe(2me)-pro-aib-phe-ome ((Sss)-8gunclassified
See 1 more Smart Citation
“…4(4) φ ( -57.4 (7) -111.0 (5) 179.4 (4) -57(1); -52 (1) -50(1); -54 (1) 49.4 (6) 45.2 (6) (2) 163 (2) 3.052 (2) 171 (2) 3.013 (2) 166 (1) (S,S)-8e 3.007 (4) 165 (4) 2.872 (4) 166 (4) …”
Section: Z-gly-(s)-phe(2me)-pro-aib-phe-ome ((Sss)-8gunclassified
“…Introduction. -Since the elaboration of the 'azirine/oxazolone method' as a convenient protocol for the synthesis of Aib-containing peptides [1][2][3], this procedure has been used successfully for the preparation of model peptides [2c] [3][4][5][6], sterically congested oligopeptides [7] [8], and peptaibols [2d] [9][10][11]. It has also been shown that the method can be adopted to solid-phase methodology [12].…”
mentioning
confidence: 99%